Red planet a colonial boy on Mars - Heinlein, Robert Anson 1907- (Scribner's Sons, 1949)
A young colonist on Mars befriends a strange round creature called Willis who gets him into trouble when he goes away to school, but whose presence and friendship finally enable the colonials to negotiate a treaty with the Martians.